2020
DOI: 10.1108/josm-12-2019-0377
|View full text |Cite
|
Sign up to set email alerts
|

Employee wellness on the frontline: an interactional psychology perspective

Abstract: PurposeEmployee wellness is vital to creating high-quality employee–customer interactions, yet frontline service workers (FLSWs) do not typically engage in, or benefit from, wellness initiatives. This paper aims to conceptually model the interactive influences of organizational and employee factors in influencing FLSW involvement in wellness programs and provides suggestions on how service organizations can enhance wellness behaviors and outcomes.Design/methodology/approachThis paper builds upon classical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Instead, authors promote enlightened management practices that invest in “positive cultures” and “inclusive leadership” (Lowe 2020) or through a growing industry of “workplace wellness programs” (Lieberman 2019). Research shows that these kinds of interventions are often ineffective, but they are also less likely to be adopted in the first place in frontline service workplaces, where jobs are more often lower wage and precarious (Solnet et al 2020). Unions can play a particularly important role in addressing root causes of stress and burnout in these workplaces, with broader benefits to public health.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, authors promote enlightened management practices that invest in “positive cultures” and “inclusive leadership” (Lowe 2020) or through a growing industry of “workplace wellness programs” (Lieberman 2019). Research shows that these kinds of interventions are often ineffective, but they are also less likely to be adopted in the first place in frontline service workplaces, where jobs are more often lower wage and precarious (Solnet et al 2020). Unions can play a particularly important role in addressing root causes of stress and burnout in these workplaces, with broader benefits to public health.…”
Section: Discussionmentioning
confidence: 99%
“…Originally focusing on minimizing health-care and insurance expenditures, organizations have also used workplace wellness programs for safety and associated preventative interventions (Christophersen et al, 2015). An organization may have the best intentions in implementing a workplace health and wellness program, but too often little attention is paid to a more comprehensive view of total worker health (Solnet et al, 2020) and the program is relegated to focusing on what is both easy and reliable to track, such as step counts (Chung et al, 2017;Song and Baicker, 2019). The hospitality industry has taken a similar limited approach to step counting as a proxy for employee health and wellness management (Solnet et al, 2020;Torres and Zhang, 2021), demonstrating a lack of a deeper commitment to employees' real concerns and expectations from a workplace health and wellness program.…”
Section: Ijchm 3310mentioning
confidence: 99%
“…An organization may have the best intentions in implementing a workplace health and wellness program, but too often little attention is paid to a more comprehensive view of total worker health (Solnet et al, 2020) and the program is relegated to focusing on what is both easy and reliable to track, such as step counts (Chung et al, 2017;Song and Baicker, 2019). The hospitality industry has taken a similar limited approach to step counting as a proxy for employee health and wellness management (Solnet et al, 2020;Torres and Zhang, 2021), demonstrating a lack of a deeper commitment to employees' real concerns and expectations from a workplace health and wellness program. Hospitality-centered research in this area has also revealed employees' expectations of a workplace health and wellness program that extends beyond step counts to include nutrition awareness, smoking cessation, stress management, and exercise programs as priorities over tracking devices (Zhang et al, 2020).…”
Section: Ijchm 3310mentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, the hospitality industry has not placed a high priority on employee health and wellness, aside from those wellness initiatives which generate a rapid return on investment [51]. This is due, in part, to resource allocation associated with thin profit margins, in which a misinformed rationale has undermined justification for employee wellness on its own merits [53,54]. Collectively, the U.S. hospitality industry is facing increasing uncertainties about its labor force in a time of heightened awareness around fair wages and forecasted increasing consumer demand [47].…”
Section: The Hospitality Industrymentioning
confidence: 99%